On the relation between affinely adjustable robust linear complementarity and mixed-integer linear feasibility problems - Christian Biefel; Martin Schmidt (Optimization Letters, 2024)
We consider adjustable robust linear complementarity problems and extend the results of Biefel et al.~(SIAM J Optim 32:152–172, 2022) towards convex and compact uncertainty sets. Moreover, for the case of polyhedral uncertainty sets, we prove that computing an adjustable robust solution of a given linear complementarity problem is equivalent to solving a properly chosen mixed-integer linear feasibility problem.
Keywords: 510; Linear complementarity problems; Adjustable robustness; Robust optimization; Mixed-integer linear optimization